Optical Correlation Tomography: Comparison of Imaging Resolution with and Without Ultrasound. (2016) - Gangadharan, K. Sagila; Mohanan, K.P.
Abstract: The non-invasive recovery of various properties of biological tissues producing cross sectional images, named as tomography, has been used in detection and diagnosis of various diseases. In this paper, we demonstrate the improvement in resolution of the optical tomography by the introduction of focussed ultrasound, thereby localising the region of imaging. Towards this, we recover the amplitude of vibration of scatterers in the presence of ultrasound and the light absorption in the absence of ultrasound and compare the images with respect to the recovery resolution. Correlation Diffusion Equation, describing the diffusive propagation of autocorrelation of light in turbid media is used as the forward model for both of the cases.